PM source apportionment analysis in the Venetian area. (1st January 2011) - Pillon, Silvia; Liguori, Francesca; Dalan, Fabio; Maffeis, Giuseppe
A CALMET-CAMx system was implemented to investigate PM10 source apportionment in the urban area of Venice. The modelling system was run for two winter months on a domain covering most of the Veneto region with a 4 km resolution mesh and a 1 km nested grid over Venice and its mainland area, in order to distinguish the local emission contributions from the regional ones. A brute-force method was applied in the nested grid: a 50% emission reduction was imposed separately for the main sectors (road transport, industrial plants, agricolture domestic heating, other transport, the latest comprehending the Venice harbour activities).